2017
DOI: 10.1186/s13068-017-0891-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermotolerant genes essential for survival at a critical high temperature in thermotolerant ethanologenic Zymomonas mobilis TISTR 548

Abstract: BackgroundHigh-temperature fermentation (HTF) technology is expected to reduce the cost of bioconversion of biomass to fuels or chemicals. For stable HTF, the development of a thermotolerant microbe is indispensable. Elucidation of the molecular mechanism of thermotolerance would enable the thermal stability of microbes to be improved.ResultsThermotolerant genes that are essential for survival at a critical high temperature (CHT) were identified via transposon mutagenesis in ethanologenic, thermotolerant Zymom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 79 publications
0
36
0
Order By: Relevance
“…This study was motivated by the surprising fact that only a few genes for RSEs and HSPs have been identified as thermotolerant genes (Charoensuk et al, 2017;Murata et al, 2018), which are essential for survival at a CHT. The finding presented suggests that many genes for RSEs and HSPs have the potential to improve the CHT, although the range of improvement is within 1 • C. It is thus likely that there are several genes that have overlapping functions in cells, and thus, the disruption of one gene is complemented by another gene.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study was motivated by the surprising fact that only a few genes for RSEs and HSPs have been identified as thermotolerant genes (Charoensuk et al, 2017;Murata et al, 2018), which are essential for survival at a CHT. The finding presented suggests that many genes for RSEs and HSPs have the potential to improve the CHT, although the range of improvement is within 1 • C. It is thus likely that there are several genes that have overlapping functions in cells, and thus, the disruption of one gene is complemented by another gene.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms intrinsically have an upper temperature limit for survival called a critical high temperature (CHT) (Matsushita et al, 2015;Kosaka et al, 2019). Genome-wide analysis of three mesophiles, Escherichia coli, Acetobacter tropicalis, and Zymomonas mobilis, by screening thermosensitive mutants either with a single-knockout mutant library or with a transposoninserted mutant library has revealed that about 1.5% of genomic genes, called thermotolerant genes, are responsible for cell survival at a CHT (Charoensuk et al, 2017;Murata et al, 2018), but there is no sufficient information to conclude that a mesophile with a larger number of genomic genes has a larger number of thermotolerant genes and thus tends to be more temperatureresistant. Other factors including gene expression of key proteins may also contribute to the degree of thermotolerance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations